Biologiku: Android-Based Biology Learning Media Integration of Science, Islam and Technology - Achmad Ali Fikri; Venty Zuslia; Muhammad Yusman; Nilam Rizkya Agustanti; Aprilisa Risky Diana; Vina Naila Muna; Lin Eflina Nailufa (Proceeding International Conference on Religion, Science and Education, 2023)
Learning is currently experiencing a shift from conventional learning in the classroom to internet-based virtual learning via mobile devices. This study aims to produce an android application for biology learning media based on android integration of science, Islam and technology that is appropriate to be implemented in high school or equivalent level. This type of research is research and development using the Borg & Gall development model with locations on the island of Karimunjawa. The research subjects included pre-service Biology teachers, Biology teachers and students, while the samples were taken from all students of class XII. The data in this study included assessment data from validators, data from preliminary trials and data from field trials which were collected using a product feasibility assessment questionnaire with the help of the Google form. Data analysis was performed using the Rasch Model assisted by the Ministep application. This research resulted in an android-based biology learning media application called "biologiku" which is appropriate, as seen from the data analysis from field trials which showed a raw variance explained by measures value of 35.4% so that it can be said that the developed application met the eligibility criteria. This research is expected to provide real benefits in the world of education as well as being a motivation for the development of media, especially those that integrate science, Islam and technology.